Virtual social interaction and loneliness among emerging adults amid the COVID-19 pandemic - Emily Towner; Livia Tomova; Danielle Ladensack; Kristen Chu; Bridget Callaghan (2022)
Many social activities moved online during the global COVID-19 pandemic, yet research investigating whether virtual social interactions facilitate social connectedness has been inconclusive. In this study, participants completed online questionnaires assessing objective social isolation, loneliness, mental health, and virtual social interactions. There was clear evidence for worsening mental health among emerging adults during the COVID-19 pandemic characterized by large increases in depressive symptoms (mean increase = 8.35, 95% CI [6.97, 9.73],